ANALISIS PROFITABILITAS, LEVERAGE, DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN - Aden Apandi; Meita Pragiwani; Fanisyah Maliki; Preztika Ayu Ardheta; Maya Mustika (LPPM Politeknik Pajajaran ICB Bandung, 2023)
This study aims to determine and analyze the effect of profitability, leverage and liquidity on company value in the Food and Beverage Subsector Manufacturing Industry IDX 2017-2021. The method used in this research is categorized as quantitative causality research, namely research to describe the condition of the company which is carried out by analysis based on the data obtained. The population in this study are companies engaged in the food and beverage consumer goods sector which are listed on the Indonesia Stock Exchange for the 2017-2021 period, totaling 20 companies. The companies used as samples have financial information data that is in accordance with the research. Based on the sample criteria, there are 20 companies engaged in the consumer goods sector that have gone public which are eligible as samples in this study. Data analysis techniques using Eviews 12.0 software to process variable data in this study were descriptive statistics, classic assumption tests, panel data regression model tests, panel data regression model selection tests, hypothesis testing, and coefficient of determination tests. The results of this study indicate that profitability and leverage have an effect on firm value, while liquidity has no effect on firm value.